Water use of Prosopis juliflora and its impacts on catchment water budget and rural livelihoods in Afar Region, Ethiopia - Hailu Shiferaw; Tena Alamirew; Sebinasi Dzikiti; Woldeamlak Bewket; Gete Zeleke; Urs Schaffner (Scientific Reports, 2021)
Abstract Dense impenetrable thickets of invasive trees and shrubs compete with other water users and thus disrupt ecosystem functioning and services. This study assessed water use by the evergreen Prosopis juliflora, one of the dominant invasive tree species in semi-arid and arid ecosystems in the tropical regions of Eastern Africa. The objectives of the study were to (1) analyze the seasonal water use patterns of P. juliflora in various locations in Afar Region, Ethiopia, (2) up-scale the water use from individual tree transpiration and stand evapotranspiration (ET) to the entire invaded area, and 3) estimate the monetary value of water lost due to the invasion. The sap flow rates of individual P. juliflora trees were measured using the heat ratio method while stand ET was quantified using the eddy covariance method. Transpiration by individual trees ranged from 1–36 L/day, with an average of 7 L of water per tree per day. The daily average transpiration of a Prosopis tree was about 3.4 (± 0.5) mm and the daily average ET of a dense Prosopis stand was about 3.7 (± 1.6) mm. Using a fractional cover map of P. juliflora (over an area of 1.18 million ha), water use of P. juliflora in Afar Region was estimated to be approximately 3.1–3.3 billion m3/yr. This volume of water would be sufficient to irrigate about 460,000 ha of cotton or 330,000 ha of sugar cane, the main crops in the area, which would generate an estimated net benefit of approximately US$ 320 million and US$ 470 million per growing season from cotton and sugarcane, respectively. Hence, P. juliflora invasion in the Afar Region has serious impacts on water availability and on the provision of other ecosystem services and ultimately on rural livelihoods.